Factors Contributing to Late Physiotherapy Intervention of Children with Cerebral Palsy at The University Teaching Hospital, Lusaka in Zambia - Chona Kanyembo; Brian Chanda Chiluba; Geoffrey Moyo (The Center for Disability Studies and Services Brawijaya University, 2021)
Introduction: Cerebral palsy is the leading cause of disability worldwide and Zambia has its fair share of cases. Most parents/caregivers of children with Cerebral palsy at University Teaching Hospital started attending physiotherapy late when their children were over one year Therefore, the aim of this study was to explore the perceptions of mothers towards factors contributing to late physiotherapy intervention of children with Cerebral palsy at University Teaching Hospital. Furthermore, assess the knowledge of mothers with children between 0-5 years on the role of physiotherapy in Cerebral palsy. Methodology: An exploratory study design using qualitative methods was used. Data collection techniques were FGDs that consisted of purposively sampling of 10 mothers of children with CP attending physiotherapy at University Teaching Hospital. Audio-recording from the FGDs was transcribed verbatim for each session by an independent person. The study employed thematic analysis for data analysis. The data was classified systematically by means of coding to identify key factors or issues such as concepts, categories, themes and the relationship between them. Results: This study identified four themes on factors that influence late physiotherapy intervention of children with Cerebral Palsy at University Teaching Hospital. These included: Socio-economic support; late referral for Physiotherapy; Caregiver's knowledge about Cerebral Palsy; and People's attitude towards Cerebral Palsy. Limited caregiver knowledge about the role of physiotherapy in Cerebral Palsy was reported to be due to; limited community awareness about physiotherapy; and lack of caregiver education. Conclusion: The present study sought to explore the perceptions of mothers towards factors contributing to late physiotherapy intervention in children with Cerebral Palsy. A diversity of factors that led to delayed intervention was highlighted. Rehabilitation professionals should be aware of the factors that impact mothers both positively and negatively in order to implement effective rehabilitation programs.